Provoked in Venice - Rudman, Mark. ([Middletown, Conn.] : Wesleyan University Press ; Hanover, N.H. : University Press of New England, 1999)
The remarkable third volume in a trilogy that includes the award-winning Rider and Millennium Hotel.
Machine generated contents note: "Normalissimo" -- Revolt -- Against Odds Against -- "Real" Revolt -- Brecht Looks at Xeriscaping With a Thought About Shelley -- Assassins -- Winter Night in the City of God -- Provoked in Venice -- Evening on the Zattere -- From What Angle -- Desert of Empire -- "Not Normalissimo" -- Venice Less and Less -- Tomahawk -- Across a Crowded Room -- Phaeton's Dream: Driving Lessons in the Desert -- Joan and Jean -- Stealth -- Last Night of a First Trip to Venice -- Without a Care in the World -- Midsummer Night in Venice -- Tell Me Why -- Early Deliveries No One Receives -- Venice: The Return in Winter I -- Venice: The Return in Winter II -- In Your Own Time.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Venice (Italy) -- Poetry; POETRY -- American -- General; Italy -- Venice; Poetry